Espécies brasileiras do gênero Hyalella (Crustacea-Amphipoda) - Pereira, Vânia Filippi Goulart Carvalho (1983)
A systematic is made of the species of Hyalella Smith (Crustacea-Amphipoda) based on material gathered at different points of the Brazilian territory, which is kept at the carcinological collection of the Museu Nacional, Rio de Janeiro. Six species were found, four of which (Hyalella azteca, H. pernix, H. warmingi, H. meinerti) have been previously recorded for Brazil and were considered new to science (H serrana, H. caeca). All are, as peculiar to the genus, fresh water dwellers, H. caeca being typically troglobitic, H. warmingi occasionally so, and the remaining ones epigean. H. longistila (Faxon) also record from Brazil, has not been found in the material studied, and therefore is not here dealed with. Besides a Key for species known to occur in Brazil, detailed descriptions and illustrations are given for each of the six species studied and also their geographical distribution and type-locality. A list is also included of the species of Hyaella of the world with record on a map of their geographical distribution. The distribution of the six brazilian species here studied, showing the localities where the specimens were collected, is also present on a separate map.